Understanding Factors that Encourage Research Productivity for Academic Librarians - Hoffmann, Kristin; Berg, Selinda; Koufogiannakis, Denise (Evidence Based Library and Information Practice, 2017)
Abstract Objective – This project identifies the factors that contribute to the success of librarians as active researchers. Research success is generally aligned with productivity and output, and the authors are therefore interested in understanding the factors that encourage research productivity. This fills a gap in the literature on librarians as researchers, which has tended to focus on barriers rather than enablers. Methods – For this quantitative study, we distributed an online survey to 1,653 potential participants across Canada and received 453 usable responses for a 27% response rate. The survey asked participants to report their research outputs and to answer questions that addressed three categories of factors: Individual Attributes, Peers and Community, and Institutional Structures and Supports. We then statistically analyzed participant responses in order to identify relationships between the research output variables (weighted output score and number of peer-reviewed articles) and the three categories, the factors within those categories, and the constituent components. Results – Participants’ research output consisted largely of presentations, non-peer-reviewed articles, peer-reviewed articles, and posters. All three categories of factors were significantly related to research output, both for a calculated weighted output score and for number of peer-reviewed articles. All of the factors identified within those categories were also significant when tested against weighted output score, but Intrinsic Motivations was not a significant factor when tested against number of peer-reviewed articles. Several components of factors were also not significant for number of peer-reviewed articles. Age was the only significant component of Demographics. Three components of Education and Experience were significant: whether participants had received research training after completing their MLIS, whether they were working on an advanced degree, and the institution where they had obtained their MLIS. Conclusions – Research productivity is significantly impacted by all three categories: Individual Attributes, Peers and Community, and Institutional Structures and Supports. Fostering an environment that focuses on all of these areas will be most likely to promote research output for librarians. At the same time, this study’s findings point to particular aspects that warrant further investigation, such as the nature and effect of institutional support and librarians’ motivations for doing research.